LEARNING TO READ WITH MONTESSORI METHOD - Faradiba Sari Harahap (Jurnal Scientia, 2022)
The ability to read is complex and detailed for early childhood children. In contrast to the ability to speak and listen which can be obtained naturally from their surroundings, the ability to read must be learned with certain methods. Montessori is a children's education method that can optimize children's potential through learning that involves children's sensory and motor aspects in a detailed and fun way. In Montessori, reading are introduced as fun and useful activities, which can help a child understand and appreciate the world, and share ideas and experience with other people. This article is written to explain how early childhood children learn to read by using the Montessori method. This research is a qualitative descriptive research. This research method is library research through data collection techniques obtained through books, journals, articles and other supporting sources. The results of this study explain that in the Montessori method, early childhood learns to read by using didactic materials in two stages namely Early Preparation Activities and Reading Activities. The Early Preparation Activities include Classified Pictures, Speech, and I spy. While the Reading Activities involve Object Boxes, Action Cards, Reading Folder, Puzzle Words, Book Corner and Library. All these activities have been sorted according to the level of difficulty from the simplest to the most complex which refer to the basic principles in Montessori Method.